2002
DOI: 10.1021/ja017641u
|View full text |Cite
|
Sign up to set email alerts
|

The First General Enantioselective Catalytic Diels−Alder Reaction with Simple α,β-Unsaturated Ketones

Abstract: General Information. Commercial reagents were purified prior to use following the guidelines of Perrin and Armarego.1 Non-aqueous reagents were transferred under nitrogen via syringe or cannula. Organic solutions were concentrated under reduced pressure on a Büchi rotary evaporator. Chromatographic purification of products was accomplished using forcedflow chromatography on ICN 60 32-64 mesh silica gel 63 according to the method of Still. were obtained from the UC Irvine Mass Spectral facility. Gas liquid chro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

5
188
0
4

Year Published

2002
2002
2016
2016

Publication Types

Select...
7
2

Relationship

3
6

Authors

Journals

citations
Cited by 452 publications
(197 citation statements)
references
References 12 publications
5
188
0
4
Order By: Relevance
“…Overall, these preliminary results indicate that the reaction works best with ␣-substituted acroleins. In this respect, the present methodology is complimentary to the innovative amine-based organocatalysts developed by MacMillan and coworkers (11,12), which is well suited for the Diels-Alder reaction of acrolein, ␤-substituted acroleins, and ␣,␤-unsaturated ketones.…”
Section: Resultsmentioning
confidence: 93%
See 1 more Smart Citation
“…Overall, these preliminary results indicate that the reaction works best with ␣-substituted acroleins. In this respect, the present methodology is complimentary to the innovative amine-based organocatalysts developed by MacMillan and coworkers (11,12), which is well suited for the Diels-Alder reaction of acrolein, ␤-substituted acroleins, and ␣,␤-unsaturated ketones.…”
Section: Resultsmentioning
confidence: 93%
“…In addition to Lewis acid catalysis, two other catalytic methods have emerged for the promotion of enantioselective DielsAlder reactions, both using metal-free, ''organic'' catalysts (9,10). MacMillan and coworkers (11,12) demonstrated a broadly useful and strategically novel approach for the asymmetric catalysis of Diels-Alder reactions. These authors showed that, in the presence of a chiral amine, ␣,␤-unsaturated aldehydes and ketones exist in equilibrium with the corresponding chiral iminium ions, which undergo diastereoselective Diels-Alder reactions.…”
mentioning
confidence: 99%
“…Despite the superficial similarities between aldehydes and ketones, these carbonyl families exhibit largely different steric and electronic properties with respect to catalyst interactions. As a consequence, the translation of enantioselective activation modes between these carbonyl subclasses is often difficult (if not unattainable in many cases) (21,22). Herein, we describe the invention of a previously undisclosed family of organocatalysts that enable cyclic ketones to successfully function within the SOMO-activation platform while being chemically robust to oxidative reagents.…”
mentioning
confidence: 99%
“…This catalysis concept was founded on the mechanistic hypothesis that the reversible formation of iminium ions from ␣,␤-unsaturated aldehydes and amines (Scheme 2) might emulate the equilibrium dynamics and -orbital electronics that are inherent to Lewis acid catalysis (Scheme 1). This new catalysis strategy has subsequently been applied to the development of a variety of enantioselective chemical processes, including cycloadditions (46,47,50), Mukaiyama-Michael additions (53), Friedel-Crafts alkylations (48,49,52), heteroconjugate additions, hydrogenations, and cascade reactions.…”
Section: Methodsmentioning
confidence: 99%